Methiothepin Suppresses Human Ovarian Cancer Cell Growth by Repressing Mitochondrion-Mediated Metabolism and Inhibiting Angiogenesis In Vivo - Jin-Young Lee; Changwon Yang; Whasun Lim; Gwonhwa Song (MDPI AG, 2020)
Ovarian cancer is the fifth leading cause of cancer-related deaths in women. Despite treatment, most patients experience relapse and the 5-year survival rate of ovarian cancer is less than 50%. Serotonin has cell growth-promoting functions in a variety of carcinomas, but the effect of serotonin receptor antagonists on ovarian cancer cells is unknown. In this study, it was confirmed that methiothepin, a serotonin receptor antagonist, suppresses the viability of, and induces apoptosis in, ovarian cancer cells. Methiothepin also induces mitochondrial dysfunction, represented by depolarization of the mitochondrial membrane and increased mitochondrion-specific Ca2+ levels, and causes metabolic disruption in cancer cells such as decreased ATP production and oxidative phosphorylation. Methiothepin also interferes with vascular development in transgenic zebrafish embryos. Combination treatment with methiothepin improves the anti-cancer effect of paclitaxel, a standard chemotherapeutic agent. In conclusion, this study revealed that methiothepin is a potential novel therapeutic agent for ovarian cancer treatment.